Measuring student attitude towards the application of gamification in the higher education classroom - van Reede van Oudtshoorn, Nicolaas N (The Independent Institute of Education, 2020)
Modern day educators face a myriad of challenges with today’s learners. The world has become a fast-paced environment with many distractions. Keeping learners focussed on inclass activities pose a challenge and a cellular phone is often an issue of contention and a burden on the concentration and focus of the learner. Gamification is the process of incorporating game elements into non-game environments (Deterding, et al., 2014). Gamification has shown positive results in the field of education and others to bring about positive change, in engagement and interaction (Deterding, et al., 2014). Using gamification, which incorporates elements and characteristics of games into every day actions, the goal is to investigate if it will capture the minds and imagination of students and help them better participate in class and help them to retain information more effectively. Students’ expressed incredibly positive feelings and emotions towards gamification and the themes picked up from the questionnaire showed encouraging emotions towards the effects and impact of gamification. Considering the findings, gamification could be a very effective and useful tool in the higher education classroom. It could help with in-class challenges and help break through to students who struggle to concentrate in class.
Keywords: Student attitudes; Gamification; Higher education; Classroom practice